Życie animowane. Autyzm opowiadany, rysowany, doświadczany - Powierska, Agnieszka (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article is based on Anabelle Honess Roe’s research in which she analysed the ways that animation is used in Roger Ross Williams’s documentary Life, Animated (2016). It studies how an individual, subjective perspective is evoked in the film. Other documentaries which use animation to tell the story about autism are mentioned as a context.